Effect of Wheat Bran Phytase Subjected to Different Conditioning Temperatures on Phosphorus Utilization by Broiler Chicks Based on Body Weight and Toe Ash Measurements - Cavalcanti, W.B.; Behnke, K.C. (International Journal of Poultry Science, 2004)
Cereal grains and oilseed byproducts are major components of diets commercially fed to poultry and swine. Although phosphorus levels are relatively high in these feedstuffs, most of it is presented as phytate and thus, unavailable to monogastric species. Wheat bran is known for having high endogenous phytase enzyme activity. This study was conducted to investigate the ability of wheat bran endogenous phytase to withstand the high temperatures associated with the pelleting process. Additionally, to evaluate the efficacy of this enzyme source in improving phytate phosphorus utilization by broiler chicks. Wheat bran was subjected to steam conditioning/pelleting at temperatures between 50 oC and 90 oC. Test diets were formulated with levels of available phosphorus (AvP) below those recommended by the NRC. Wheat bran was incorporated into test diets at 5% inclusion level in either the unprocessed form or after being subjected to steam conditioning at 60 oC and 80 oC followed by pelleting. Live weight gain, feed efficiency and toe ash measurements were observed as response variables to available phosphorus in the diets. Considerable losses in endogenous phytase activity in wheat bran were observed after steam conditioning at the aforementioned temperatures. However, based on the observations, the inclusion of wheat bran in the unprocessed form positively influenced the bird`s ability to utilize phosphorus present in the diet.